The patient education — Learning and Coping Strategies — improves adherence in cardiac rehabilitation (LC-REHAB): A randomised controlled trial. (1st June 2017) - Lynggaard, Vibeke; Nielsen, Claus Vinther; Zwisler, Ann-Dorthe; Taylor, Rod S.; May, Ole
Abstract: Background: Despite proven benefits of cardiac rehabilitation (CR), adherence to CR remains suboptimal. This trial aimed to assess the impact of the patient education 'Learning and Coping Strategies' (LC) on patient adherence to an eight-week CR program. Methods: 825 patients with ischaemic heart disease or heart failure were open label randomised to either the LC arm (LC plus CR) or the control arm (CR alone) across three hospital units in Denmark. Both arms received same amount of training and education hours. LC consisted of individual clarifying interviews, participation of experienced patients as co-educators, situational, reflective and inductive teaching. The control arm received structured deductive teaching. The primary outcomes were patient adherence to at least 75% of the exercise training or education sessions. We tested for subgroup effects on the primary outcomes using interaction terms. The primary outcomes were compared across arms using logistic regression. Results: More patients in the LC arm adhered to at least 75% of the exercise training sessions than control (80% versus 73%, adjusted odds ratio (OR):1.48; 95% CI:1.07 to 2.05, P  = 0.018) and 75% of education sessions (79% versus 70%, adjusted OR:1.61, 1.17 to 2.22, P  = 0.003). Some evidence of larger effects of LC on adherence was seen for patients with heart failure, low education and household income. Conclusions: Addition of LC strategies improved adherence in rehabilitation both in terms of exercise training and education. Patients with heart failure, low levels of education and household income appear to benefit most from this adherence promoting intervention. Trial registration: www.clinicaltrials.gov identifierNCT01668394